(untitled) (Research, Society and Development, 2024)
Anticoagulant medications play a fundamental role in the treatment of several conditions associated with thrombotic risk, such as coronary artery disease and venous thrombosis, although their main adverse effect is the risk of hemorrhage. In this study, we focused on the evaluation of several anticoagulant medications, including acetylsalicylic acid (Aspirin®, Tromalyt®), clopidogrel (Plavix®, Iscover®), vitamin K antagonists such as Warfarin (Warfarine®, Marevan®), and NOACs such as Dabigatran (Pradaxa®), Rivaroxaban (Xarelto®), Edoxaban (Lixiana®) and Apixaban (Eliquis®). The importance of individualized planning in the dental treatment of these patients was highlighted. The objective of this study was to present safe protocols available for the dental management of patients using oral anticoagulants. An integrative literature review was carried out, carefully selecting national and international articles to analyze the influence of these medications on oral surgical procedures. Disagreements were found between authors, with some suggesting that suspending medication is not feasible due to the risks, while others emphasize an individualized approach, suspending medication if necessary, together with the doctor. It was concluded that the number of patients using anticoagulants is on the rise and, therefore, it is crucial that dental surgeons are prepared to provide safe care, thus minimizing the risk of bleeding complications.